Lifestyle-Related Factors in the Self-Management of Chemotherapy-Induced Peripheral Neuropathy in Colorectal Cancer: A Systematic Review. (16th March 2017) - Derksen, Tess M. E.; Bours, Martijn J. L.; Mols, Floortje; Weijenberg, Matty P.
Abstract : Background. Chemotherapy-induced peripheral neuropathy (CIPN) is a common adverse effect of chemotherapy treatment in colorectal cancer (CRC), negatively affecting the daily functioning and quality of life of CRC patients. Currently, there are no established treatments to prevent or reduce CIPN. The purpose of this systematic review was to identify lifestyle-related factors that can aid in preventing or reducing CIPN, as such factors may promote self-management options for CRC patients suffering from CIPN. Methods. A literature search was conducted through PubMed, Embase, and Google Scholar. Original research articles investigating oxaliplatin-related CIPN in CRC were eligible for inclusion. Results. In total, 22 articles were included, which suggested that dietary supplements, such as antioxidants and herbal extracts, as well as physical exercise and complementary therapies, such as acupuncture, may have beneficial effects on preventing or reducing CIPN symptoms. However, many of the reviewed articles presented various limitations, including small sample sizes and heterogeneity in study design and measurements of CIPN. Conclusions. No strong conclusions can be drawn regarding the role of lifestyle-related factors in the management of CIPN in CRC patients. Certain dietary supplements and physical exercise may be beneficial for the management of CIPN, but further research is warranted.